1997
DOI: 10.1541/ieejsmas.117.407
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Fabricate Metal Tips for Scanning Probe Microscopy

Abstract: We present a new method to fabricate sharp metal tips on cantilevers for a SPM. The metal tip, which is deposited and patterned as a film on a silicon mold with pyramidal etch pits, is attached by metal-to-metal bonding to a metal pad on a substrate. Then the tip on the substrate is peeled off the mold at room temperature. The tip surface is very smooth without grain boundaries associated with deposited thin films. A platinum tip with a radius curvature of less than 15nm was successfully fabricated. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…• solder (using thin-film deposited solders or preforms) [1], [62]; • polymer [63]; • low melting temperature glasses (including glass frits) [1], [4]; • thermocompression (using soft metal thin films) [35], [64], [65]. The eutectic bond was explored extensively by Ko and coworkers for the packaging of pressure sensors.…”
Section: Intermediate-layer Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…• solder (using thin-film deposited solders or preforms) [1], [62]; • polymer [63]; • low melting temperature glasses (including glass frits) [1], [4]; • thermocompression (using soft metal thin films) [35], [64], [65]. The eutectic bond was explored extensively by Ko and coworkers for the packaging of pressure sensors.…”
Section: Intermediate-layer Bondingmentioning
confidence: 99%
“…The bond has been tested in lap shear and has bond strengths comparable to that of wire bonds. Recently, a metal structure transfer process has been demonstrated that utilizes a similar process [65].…”
Section: Intermediate-layer Bondingmentioning
confidence: 99%
“…A variety of fabrication processes for AFM cantilevers have been reported in literature, but most of the cantilevers presented in these articles are often greater than 100 lm (Folch et al 1997;Albrecht et al 1990;Yagi et al 1997;Brugger et al 1992;Tabak et al 2010;Rogers et al 2003) and fabricated with comparable huge tolerances insufficient for cantilevers smaller than 20 lm (Viani et al 1996). The manufacturing of small cantilevers, described also in some papers, uses similar manufacturing processes with similar tolerances or an inadequate cantilever material, like polyimide or gold.…”
Section: Introductionmentioning
confidence: 99%
“…Due to properties including low electron affinity and high thermal conductivity, diamond rapidly became the material of most interest. 10 These were studied for flat panel displays 22 and also to produce tips for atomic force microscopy and scanning tunneling microscopy 23 and for scanning near-field optical microscope. 16 Other materials reported were WSi, 19 SiC, 20 NbN, 21 and modified photoresist.…”
Section: Introductionmentioning
confidence: 99%
“…25 In double-gate FEAs, loss of anode current, either by suppression of field emission from the tip or repulsion of electrons into the extraction electrode, could present a problem, depending on the strength of the focusing field. 33 Elimination of cross-talk in field emitter displays 31 and sources for multibeam electron beam lithography 23 were seen as potential applications. 27 To reduce the repulsive effect, it was proposed 28 to use a much larger diameter focusing aperture, partway to an in-plane scheme despite the disadvantage of reduced tip density.…”
Section: Introductionmentioning
confidence: 99%